Covering the United States Supreme Court in the digital age / edited by Richard Davis, Brigham Young University. - Davis, Richard, 1955- (Cambridge University Press, 2014)
The US Supreme Court seeks to withhold information about its deliberations, while the press's job is to report and disseminate this information. These two objectives conflict and create tension between the justices and the reporters who cover them; add to that the increasing demands for transparency in the digital age and the result is an interesting dynamic between an institution that seeks to preserve its opaqueness and a press corps that demands greater transparency. This volume examines the relationship between justices and the press through chapters that discuss facets such as coverage of the institution, the media's approach to the docket, and the effects of news coverage on public opinion. Additionally, two journalists who cover the court offer insights into the profession of reporting today, while two biographers of Supreme Court justices share the perspectives of those justices regarding the press.